Cause of Defect Analysis in the Assembly Process of K15 Type Motor Machine Components Installation Using Fmea Method in PT XYZ - Kholil, Muhammad; Hidayat, Atep Afia; ., Friendy (Teknik dan Ilmu Komputer, 2016)
AbstrakÃÂ Komponen mesin motor adalah kebutuhan yang paling penting pada suatu produk sepeda motor. Failure Mode and Effect Analysis (FMEA) merupakan suatu cara dimana suatu bagian atau suatu proses yang mungkin gagal memenuhi suatu spesifikasi, menciptakan cacat atau ketidaksesuaian, dan dampaknya pada pelanggan bila mode kegagalan itu tidak dicegah atau dikoreksi. Kegagalan produk yang sering muncul adalah cacat pada saat proses pencetakan nomor mesin pada Cover L bernilai RPN sebesar 504, proses pengeleman pada Crank Case bernilai RPN sebesar 448, proses pengukuran celah katup Cylinder Head bernilai RPN sebesar 392, dan proses pemasangan Oil Pump terhadap Cover Reed Valve bernilai RPN sebesar 448. FMEA merupakan metode yang menjadi pilihan untuk mengurangi tingkat kecacatan atau kegagalan produk dengan menitikberatkan pada penanggulangan faktor-faktor yang memiliki potensi menyebabkan kegagalan produk.ÃÂ Kata Kunci: FMEA, RPN, Quality.ÃÂ ÃÂ AbstractÃÂ Engine Components is the most important requirement of a motorcycle product. FMEA is a method in which a part or a process that might fail to meet specifications, resulting a defect or nonconformity which may impact on the customer when the failure mode is not prevented or corrected. Product failures that often arise are defects at the printing process of the machine number on Cover L with RPN value of 504, the gluing process on Crank Case with RPN value of 448, the measurement process ofÃÂ Cylinder Head valve gap with the RPN value of 392, and the Oil Pump installation process on the Cover Reed valve with RPN value of 448. Failure Mode and Effect Analysis ( FMEA ) is the chosen method to reduce the defect rate or failure of a product by focusing on overcoming the factors that can potentially lead to product failure.ÃÂ Keyword: FMEA (Failure Mode and Effect Analysis), RPN (Risk Priority Number), QualityÃÂ